2000
DOI: 10.1046/j.1365-2583.2000.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of phlebotomine sandflies inferred from small subunit nuclear ribosomal DNA

Abstract: Relationships among seventy specimens, fifteen species and three genera of phlebotomines were inferred from the phylogenetic analysis of small subunit nuclear rDNA, obtained by the PCR amplification and cloning of almost full-length genes. Outgroups included fifteen dipterans, and single representatives of four other insect orders. The more distant the taxa compared, the larger were the regions of ambiguous sequence alignment that needed to be deleted in order to avoid circularity in performing parsimony analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 25 publications
7
54
0
Order By: Relevance
“…A total of 83 intraspecific studies has been recorded in the literature (Esseghir et al, 1997;Marcondes et al, 1997;Dias et al, 1998;Aransay et al, 2000Aransay et al, , 2003Di Muccio et al, 2000;Esseghir and Ready, 2000;Mukhopadhyay et al, 2000;Yin et al, 2000;Marquez et al, 2001;Soto et al, 2001;Arrivillaga et al, 2002Arrivillaga et al, , 2003Bauzer et al, 2002a,b;Depaquit et al, , 2004aDepaquit et al, , 2005bDepaquit et al, , 2008bDepaquit et al, , 2013Depaquit et al, , 2014Hodgkinson et al, 2002Hodgkinson et al, , 2003Testa et al, 2002;Bottecchia et al, 2004;Margonari et al, 2004;Pesson et al, 2004;Yahia et al, 2004;Elnaiem et al, 2005;Meneses et al, 2005;Perrotey et al, 2005;Dvorak et al, 2006Dvorak et al, , 2011Mazzoni et al, 2006Mazzoni et al, , 2008de Souza Rocha et al, 2007;Hamarsheh et al, 2007;Moin-Vaziri et al, 2007a,b;Baron et al, 2008;Bounamous et al, 2008Bounamous et al, , 2014Lins et al, 2008…”
Section: Resultsmentioning
confidence: 99%
“…A total of 83 intraspecific studies has been recorded in the literature (Esseghir et al, 1997;Marcondes et al, 1997;Dias et al, 1998;Aransay et al, 2000Aransay et al, , 2003Di Muccio et al, 2000;Esseghir and Ready, 2000;Mukhopadhyay et al, 2000;Yin et al, 2000;Marquez et al, 2001;Soto et al, 2001;Arrivillaga et al, 2002Arrivillaga et al, , 2003Bauzer et al, 2002a,b;Depaquit et al, , 2004aDepaquit et al, , 2005bDepaquit et al, , 2008bDepaquit et al, , 2013Depaquit et al, , 2014Hodgkinson et al, 2002Hodgkinson et al, , 2003Testa et al, 2002;Bottecchia et al, 2004;Margonari et al, 2004;Pesson et al, 2004;Yahia et al, 2004;Elnaiem et al, 2005;Meneses et al, 2005;Perrotey et al, 2005;Dvorak et al, 2006Dvorak et al, , 2011Mazzoni et al, 2006Mazzoni et al, , 2008de Souza Rocha et al, 2007;Hamarsheh et al, 2007;Moin-Vaziri et al, 2007a,b;Baron et al, 2008;Bounamous et al, 2008Bounamous et al, , 2014Lins et al, 2008…”
Section: Resultsmentioning
confidence: 99%
“…(Phlebotomus) papatasi (Missiroli, 1929) is also questioned, since the two phlebotomine genera do not form a monophyletic clade (Aransay et al, 2000). Due to the differences in the life cycle, morphology, and dimensions of gamonts, gametocysts and particularly oocysts, and the results of cross-infection studies and molecular phylogenetic analysis, we clearly demonstrated that gregarines from Ph.…”
Section: Ph Sergentimentioning
confidence: 74%
“…This well-defined group is likely to have a monophyletic origin with adaptation to diverse environments and today they are found in temperate regions but most species presents tropical and subtropical distribution [8,9].…”
Section: Introductionmentioning
confidence: 99%